Production of humic substances from cotton stalks biochar by fungal treatment with Ceriporiopsis subvermispora. (February 2016) - Placido, Jersson; Capareda, Sergio; Karthikeyan, Raghuparty
Abstract: This study evaluated the biodepolymerization of biochar from cotton stalks gasification using four fungal strains Phanerochaete chrysosporium, Ceriporiopsis subvermispora, Postia placenta, and Bjerkandera adusta . After the biological treatment, the liquid and solid phases were analyzed using UV–Vis and FT-IR spectroscopy. The biochar's largest depolymerization was obtained by C. subvermispora . The depolymerization kinetic of C. subvermispora showed the production of laccase and manganese peroxidase and a correlation between the depolymerization and the production of ligninolytic enzymes. The highest production of ligninolytic enzymes and depolymerization was observed after 24 days. The modifications in the UV–Vis and FT-IR spectra exhibited the presence of functional groups related with humic substances from cultures with C. subvermispora and cotton stalks biochar.